Waste Mg-Al based alloys for hydrogen storage. (23rd August 2018) - Hardian, R.; Pistidda, C.; Chaudhary, A.-L.; Capurso, G.; Gizer, G.; Cao, H.; Milanese, C.; Girella, A.; Santoru, A.; Yigit, D.; Dieringa, H.; Kainer, K.U.; et al.
Abstract: Magnesium has been studied as a potential hydrogen storage material for several decades because of its relatively high hydrogen storage capacity, fast sorption kinetics (when doped with transition metal based additives), and abundance. This research aims to study the possibility to use waste magnesium alloys to produce good quality MgH2 . The production costs of hydrogen storage materials is still one of the major barriers disabling scale up for mobile or stationary application. The recycling of magnesium-based waste to produce magnesium hydride will significantly contribute to the cost reduction of this material. This study focuses on the effect of different parameters such as the addition of graphite and/or Nb2 O5 as well as the effect of milling time on the material hydrogenation/de-hydrogenation performances. In addition, morphology and microstructural features are also evaluated for all the investigated materials. Highlights: Mg-Al based wastes are potential hydrogen storage materials. The prepared materials have high hydrogen storage capacities (up to 6 wt%). The material is highly reversible upon cycling.